Dynamics of Indonesian Hajj and Umrah Management in Communicating with Local Residents of Saudi Arabia - Ibnu Chanif, Moch.; Tijani, Ahmad; Basofitrah, Achmad (Golden Ratio of Data in Summary, 2024)
The importance of being able to communicate in Arabic for Hajj and Umrah pilgrims when they are in the holy land of Mecca to carry out the Hajj and Umrah pilgrimages at least the congregation knows some Arabic vocabulary to avoid unwanted things such as feeling cheated, tricked, currency differences in transactions and when lost do not know the way home. The purpose of this study is to find out the Hajj and Umrah pilgrims when communicating with residents of Saudi Arabia. In this study, we as researchers used a descriptive qualitative method entitled “Dynamics of Indonesian Hajj and Umrah Management in Communicating with Local Residents of Saudi Arabia (Case Study of Alumni of PT. Nur Haramain Mulia). The researcher's process in obtaining data is observation (direct) through interviews (interviews) with Hajj and Umrah pilgrims. From the results of the interview, the congregation communicates with the Arab population using sign language by showing something as the desired destination. the Arab population generally uses ammiyah Arabic communication while the congregation uses fushah Arabic communication for those who can already communicate in Arabic. The suggestion from the congregation is that the travel party prepare earphones that will be used by the congregation so that communication between the congregation and TG runs smoothly while in Saudi Arabia. One of the pilgrims complained that the earphones used by the congregation were intermittent. In addition, although the congregation is not required to understand Arabic communication, at least the congregation has a little Arabic, it is feared that something unwanted will happen such as feeling cheated, cheated, about currency differences in transactions, and when lost not knowing the way home